Epistolary greetings in the Oxyrhynchus Papyri - Head, P (Tyndale House, 2019)
This paper examines the function of greetings in the Oxyrhynchus Papyri by focusing on vocabulary, how individuals and groups of people are described, questions relating to format and presentation, differences in format, particularly when greetings are interrupted, and the function of greetings in consolidating and maintaining connections between writers and extended communities. It offers conclusions concerning the placement of greetings, the normal epistolary practice of Graeco-Roman antiquity, and the flexibility in the relationship between the greetings, the situation and main purpose of the letter. Included is a list of the 74 letters studied and the text of their greetings.